2015
DOI: 10.1016/j.stem.2015.01.015
|View full text |Cite
|
Sign up to set email alerts
|

A Continuous Molecular Roadmap to iPSC Reprogramming through Progression Analysis of Single-Cell Mass Cytometry

Abstract: SUMMARY To analyze cellular reprogramming at the single-cell level, mass cytometry was used to simultaneously measure markers of pluripotency, differentiation, cell-cycle status, and cellular signaling throughout the reprogramming process. Time-resolved progression analysis of the resulting data sets was used to construct a continuous molecular roadmap for three independent reprogramming systems. Although these systems varied substantially in Oct4, Sox2, Klf4, and c-Myc stoichiometry, they presented a common s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
218
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(232 citation statements)
references
References 57 publications
11
218
0
Order By: Relevance
“…A recent study that investigated the effect of signalling pathways in end-stage reprogramming cells revealed that PI3K/AKT/mTOR is absolutely required for the generation and maintenance of iPSCs (Zunder et al, 2015). This is consistent with the role of this pathway in maintaining ESC pluripotency.…”
Section: Box 2 Autophagysupporting
confidence: 68%
“…A recent study that investigated the effect of signalling pathways in end-stage reprogramming cells revealed that PI3K/AKT/mTOR is absolutely required for the generation and maintenance of iPSCs (Zunder et al, 2015). This is consistent with the role of this pathway in maintaining ESC pluripotency.…”
Section: Box 2 Autophagysupporting
confidence: 68%
“…SPADE can also be adapted to analyze time-series MCM data. Recently, a modified version of the SPADE algorithm by Zunder et al 20 , called FLOW-MAP, was published. This algorithm replaces the default MST with a highly connected graph structure, in which the number of connections between cell clusters is determined by a local density.…”
Section: Up-samplingmentioning
confidence: 99%
“…The extra time dimension allows for a 3D visualization of SPADE. In the study by Zunder et al 20 , FLOW-MAP was applied to mouse embryonic fibroblasts to study the dynamic changes occurring during cellular reprogramming.…”
Section: Up-samplingmentioning
confidence: 99%
“…Using CyTOF, the Nolan group published a time resolved molecular roadmap to iPSC reprogramming (15) and identified previously unappreciated intermediate cellular states with distinct subsequent differentiation fates, suggesting that such a system can be applied to study cancer progression. Although practically more challenging for analyzing solid tumors, additional applications of the CyTOF strategy can be envisioned for solid tumor research (including brain cancers), in a way similar to recently reported single cell transcriptomics studies for glioblastoma (16).…”
Section: Coordinated Analysis Of Single Cell Proteomics Data Formentioning
confidence: 99%